Distanced Self-Talk Enhances Goal Pursuit to Eat Healthier. (March 2020) - Furman, Celina R.; Kross, Ethan; Gearhardt, Ashley N.
Attempts to make healthier food choices often fail, particularly for people who are actively trying to diet. Distanced self-talk—using one's name and non-first-person-singular pronouns (vs. first-person pronouns) to reflect on the self—provides a relatively effortless self-control tool that enhances goal pursuit. We investigated whether distanced (vs. immersed) self-talk would enhance goal pursuit to eat healthier using a novel experimental design ( N = 244). Findings indicated that dieters benefited the most from the combined use of distanced self-talk and a health prime. Nondieters made healthier choices when using distanced self-talk regardless of whether they were primed with a health goal or not. These findings suggest that distanced self-talk may constitute a self-control strategy that encourages healthier eating and highlight the need for future research to examine its translational potential.